The determinants of happiness in 12 developing Asia countries using panel data / Farah Liana Mohamad Shahari - Mohamad Shahari, Farah Liana (Faculty of Business and Management, 2020)
This study investigates the determinants of happiness in 12 developing Asia countries. Determinants included in this research are unemployment rate, financial freedom index, competitiveness index, Internet subscribers per population and political stability index. This research focus on finding the significant relationship between happiness index and the determinants listed above. Panel Regression Analysis is employed and it is found that there is significant negative relationship between unemployment rate and happiness index. Internet subscribers per population, also found to be significant with happiness index. While political stability has a significant positive relationship with happiness index. Hypotheses testing were discussed and recommendations are highlighted at the end of this study.